Monitoring of inflammatory bowel disease in 2019: A French consensus for clinical practice. Issue 7 (July 2020) - Bonnaud, Guillaume; Bouhnik, Yoram; Hagege, Hervé; Hebuterne, Xavier; Pariente, Benjamin; Roblin, Xavier; Peyrin-Biroulet, Laurent
Abstract: For inflammatory bowel disease, traditional dose escalation approaches that are based on clinical symptoms are being replaced by more aggressive treat-to-target approaches, in which treatment is adjusted promptly when predefined clinical and mucosal targets are not met. There is, however, an ongoing need to combine up-to-date treat-to-target strategies with easy-to-implement recommendations. Herein, we present consensus-recommendations for treatment targets that reflect current best practices in France. Methods Thirty-four gastroenterologists practicing in France participated in a meeting during which consensus statements about treat-to-target strategies for following patients with Crohn's disease (CD) and ulcerative colitis were developed. Targets, their definitions, and the timeframes for reaching them were defined. Consensus was defined as ≥66% of experts agreeing with a statement. Results For both diseases, the agreed targets were: patient related outcomes on disease (PRO-1), patient related outcomes on gastrointestinal symptoms (PRO-2), endoscopic healing and biomarkers of inflammation. Nutritional status has been defined as a target for CD only. Histological healing and transmural healing were not defined as targets. Deadlines to achieve targets and monitoring frequency have been agreed as well. Conclusions These consensus statements provide simple, easy-to-follow guidelines that should help gastroenterologists in France implement treat-to-target approaches, optimize treatments, and thus, reduce the burden of disease.